Monetary theory, 1601-1758 - Murphy, Antoin E.; Sugiyama, Chūhei 1921- (Routledge, 1996)
This six-volume set contains the writings of the earliest pioneers of monetary theory. It contains some 28 texts, beginning with Gerard de Maynes' "A Treatise of the Canker of England's Common Wealth" (1601) and ending with Joseph Harris' "An Essay on Money and Coins" (1757/58).